Vertical Second Harmonic Generation in Asymmetric Dielectric Nanoantennas - Davide Rocco; Carlo Gigli; Luca Carletti; Giuseppe Marino; Maria Antonietta Vincenti; Giuseppe Leo; Costantino De Angelis (IEEE Photonics Journal)
High-permittivity III–V semiconductor nanocavities have shown huge potential for enhanced nonlinear light–matter interactions at the nanoscale. In particular, Second Harmonic (SH) generation in AlGaAs nanoantennas can be extremely efficient; however, vertical emission is difficult to achieve, due to the zincblende χ(2) tensor and epitaxially growth on (100) substrates. Here, we demonstrate that we can shape the second harmonic radiation pattern from a single AlGaAs nanostructure by exploiting a geometrical symmetry breaking optimization approach. The optimized design allows to redirect the SH signal toward the normal direction and to increase the SH power collection efficiency by 2 orders of magnitude in a small numerical aperture of 0.1 with respect to the symmetrical counterpart structure.